Laporan Evaluasi Program Anak Usia Dini (PAUD) PKBM Bina Cipta Ujung - Safiiqoh Munawaroh, Sunni; Indonesia (Universitas Negeri Surabaya, 2024)
Nowadays, education has many challenges along with the development of the times, cultural diversity, financial competition and technological developments, so that it will affect the education system and needs that must be provided to students, especially for students in Early Childhood Education (PAUD). PAUD with good quality can provide benefits in the short and long term for the life of the child. Therefore, the quality of PAUD provision must still be improved in line with increased access, among others by standardizing PAUD services. The implementation of this program evaluation is expected to produce an appropriate assessment of the implementation of the ECD program regarding the strengths and weaknesses in its implementation. The method used in this study is a program evaluation of the CIPP model (Context, Input, Process and Product). This research was conducted at Kober Melati Putih PKBM Bina Cipta Ujungberung, the results of the program evaluation at this PAUD show that the implementation of PAUD programs at PKBM Bina Cipta Ujungberung is running well and meets almost all PAUD reference standards.